The Success of Corticosteroid Therapy for Visual Outcome and Choroidal Tubercle Regression on Paradoxical Reaction in Tuberculous Lymphadenitis - Vita Rahayu; St Soraya Taufik; Junaedi Sirajuddin; Hasnah Eka (Ridwan Institute, 2021)
Paradoxical reaction is worsening effect of pre-existing lesion or development new lesion. Commonly occured in extrapulmonary tuberculosis, about 20-30% in tuberculous lymphadenitis, showed by development of posterior uveitis like choroidal tubercle. A 32-year-old man presented with sudden loss vision and central scotoma on his left eye 1 day before admission. The patient got anti therapy tuberculosis by pulmonologist in one month previously for his tuberculous lymphadenitis. Our examinations revealed tuberculosis infection with swollen disc and choroidal tubercle that affected the worsening of visual acuity until 2/60 in the left eye. Based on clinical picture and history of treatment before, we decided the patient had paradoxical reaction. Topical and oral corticosteroid therapy with continuation of anti-tuberculosis therapy referred significant improvement toward visual outcome untill 20/20 and posterior pole condition on 4 months. Paradoxical reaction in tuberculous lymphadenitis is not well understood, it may caused by bacterial spreading or hypersensitivity responses. Corticosteroid therapy with continuation of anti-tuberculosis therapy recommended to help improvement visual acuity by reducing inflammation and hypersensitivity response in patient tuberculous lymphadenitis with paradoxical reaction. This is proved by improvement visual acuity and choroidal tubercle regression in our patient. Intraocular lesion can be caused by paradoxical reaction in tuberculous lymphadenitis. Early diagnosed and early corticosteroid therapy may help to sight saving.